Short leash : a memoir of dog walking and deliverance - Gary, Janice (Michigan State University Press, 2013)
"Janice Gary never walked alone without a dog - a big dog. Once, she was an adventurer, a girl who ran off to California with big dreams and hopes of leaving her past behind. But after a brutal rape, her youthful bravado vanished, replaced by a crippling need for safety. When she rescues a gangly Lab-Rottweiler pup, Gary is sure she's found her biggest protector yet. But after Barney is attacked by a vicious dog, he becomes a clone of his attacker, trying to kill any dog that comes near him. Walking with Barney is impossible. Yet walking without him is unthinkable. After years of being exiled by her terror and Barney's defensiveness, Janice risks taking her dog to a park near the Chesapeake Bay. There, she begins the messy, lurching process of walking into her greatest fears. As the leash of the past unravels, Barney sheds the defensive behaviors that once shackled him and Gary steps out of the self-imposed isolation that held her captive for three decades. Beautifully written, Short Leash is much more than a "dog story" or a book about recovering from trauma. It is a moving tale of love and loss, the journey of a broken soul finding its way toward wholeness"--Publisher's description.